2007
DOI: 10.1021/ie060287u
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Application of Enzyme Carbonic Anhydrase for CO2 Sequestration Purposes

Abstract: Biological sequestration of carbon dioxide (CO2) in geological formations is one of the proposed methods to reduce the carbon dioxide released into the atmosphere. In this method, an enzyme is used to enhance the hydration and subsequent precipitation of CO2. In the present work, the effect of bovine carbonic anhydrase on the hydration of CO2, and its precipitation in the form of calcium carbonate, was studied. The enzyme enhanced the hydration reaction. The rate of hydration reaction increased with both the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
172
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(177 citation statements)
references
References 10 publications
4
172
1
Order By: Relevance
“…This is the usual studies in biocatalytic CaCO 3 crystallization at lower pHs as generally reported in the literature. 12,13,34,54,56,57 However, when CA is active at higher pHs and the HCO 3 − ion concentration increases rapidly, the CA now operates in the opposite direction and dehydrates the HCO 3 − ions to produce CO 2 . 46 The CO 2 (aq) can then follow other paths as shown in Figure 4 and end up in CaCO 3 crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…This is the usual studies in biocatalytic CaCO 3 crystallization at lower pHs as generally reported in the literature. 12,13,34,54,56,57 However, when CA is active at higher pHs and the HCO 3 − ion concentration increases rapidly, the CA now operates in the opposite direction and dehydrates the HCO 3 − ions to produce CO 2 . 46 The CO 2 (aq) can then follow other paths as shown in Figure 4 and end up in CaCO 3 crystallization.…”
Section: Resultsmentioning
confidence: 99%
“…Although CA accelerates the rate of the CO 2 hydration reaction, it does not affect the equilibrium between the different species of carbonate (43). In a closed system, the final amount of precipitated CaCO 3 does not depend on whether the reaction is catalyzed by CA or not (10,12). Therefore, we focused on the ability of the whole-cell biocatalyst to improve the precipitation (mineralization) rate rather than measure the quantity of the resulting precipitate.…”
Section: Resultsmentioning
confidence: 99%
“…Purified CA enzymes from natural sources or from recombinant strains have been used in those studies (9)(10)(11)(12)(13). Immobilization techniques to enhance stability and reusability have also been investigated (14,15).…”
mentioning
confidence: 99%
“…Lackner et al 1995 introduced a number of chemical and physical methods to increase the rate of the process by accelerating the weathering rate of silicate minerals and precipitation rate of carbonate minerals (Lackner et al, 1995). Application of biological processes has also shown to be a cost-effective approach for accelerating CO 2 sequestration by mineral carbonation (Bennett et al, 2001;Cailleau et al, 2004;Castanier et al, 1999;Huijgen et al, 2003;Mirjafari et al, 2007;Pokrovsky et al, 2009). Four biotechnological processes of: anaerobic digestion (AD), nitrogen removal, desulfurization and bioelectrochemical systems characterized by a sequence of an acid-and an alkalinity-producing steps were specified to be able to adopt the mineral CO 2 sequestration process (Salek et al, 2013b).…”
Section: Mineral Carbonation Of Co 2 By Biotechnological Processesmentioning
confidence: 99%